prove that cosx\(sinx+cosy)+cosy\(siny-cosx)=cosx\(sinx-cosy)+cosy\(siny+cosy)

Guide :

prove that cosx\(sinx+cosy)+cosy\(siny-cosx)=cosx\(sinx-cosy)+cosy\(siny+cosy)

this is trigonemetry prove such a challenging problem of grade nine

Research, Knowledge and Information :


Sinx+siny=a and cosx+cosy=b find cosx+y ? | Socratic


cos(x+y)=(b^2-a^2)/(b^2+a^2). sinx+siny=a rArr 2sin((x+y)/2)cos ... (cosx+cosy)^2=b^2# #->cos^2x+2cosxcosy+cos^2y=b^2# ... How to prove the equality #(tan^2x+1)*cos ...
Read More At : socratic.org...

Trigonometric Identities and Formulas - analyzemath.com


... (X + Y) = cosX cosY - sinX sinY cos(X - Y) = cosX cosY + sinX sinY sin ... cos 2 X - cos 2 Y = - sin(X + Y)sin(X - Y) cos 2 X - sin 2 Y = cos(X + Y)cos(X - Y)
Read More At : www.analyzemath.com...

Prove: cos(x+y)cosy + sin(x + y)siny = cosx | eNotes


... cos(x+y)cosy + sin(x + y)siny = cosx' and find homework help for other ... How to prove the identity `sin^2x + cos^2x ... eNotes.com is a resource used daily ...
Read More At : www.enotes.com...

If sinx+siny=a and cosx+cosy=b how do you find x,y ? | Socratic


Given sinx+siny=a.....(1) cosx+cosy=b.....(2 ... Featured answers represent the very best answers the Socratic community ... How do you prove #cot^2x - cos^2x = cot ...
Read More At : socratic.org...

Prove cos(x+y) = cosx.cosy - sinx.siny - OpenStudy


Prove cos(x+y) = cosx.cosy - sinx.siny. Mathematics ... Now to find \(cos(A + B)\) use: \(cos(A - (-B))\) \ (cos(A)cos(-B) + sin(A)sin(-B ...
Read More At : openstudy.com...

Prove the identity: (cosx + cosy)^2 + (sinx - siny)^2 = 2 + 2 ...


Prove the identity: (cosx + cosy)^2 + (sinx - siny) ... (cosx + cosy)^2 + (sinx - siny)^2 = 2 + 2 cos (x+y). 1. Ask for details ; ... (cos x +cos y)^2+(sin x-sin y)^2
Read More At : brainly.com...

Suggested Questions And Answer :


Prove that G has exactly gcd(m,n) elements a such that a^m = e.?

Could I see how your teacher proved the original problem to see the clue?
Read More: ...

Prove that x ± y = b?

looking back the basic concepts of analytic geometry..we can say that x+-y=b if and only if the slope interception is being decline by the two roots of the function of x...its too complicated but..its impossible to prove that equation.
Read More: ...

Prove that <ARQ=<BQR

Read More: ...

(sin alpha-cos alpha +1)÷(sin alpha + cos alpha -1)=(sin alpha + 1)÷(cos alpha)

Question: Prove the identity (sin alpha-cos alpha +1)÷(sin alpha + cos alpha -1)=(sin alpha + 1)÷(cos alpha). Cross-multiply, to get (sin(α) –  cos(α) + 1)*cos(α) = (sin(α) + cos(α) –  1)*(sin(α) + 1) Multiplying out and re-arranging, sin(α).cos(α) –  cos^2
Read More: ...

if u=f(r) prove that

The Question: if u=f(r) prove that  d2u/dx2+d2u/dy2=f"(r)+1/r f'(r) where r=(x2+y2)½. The Solution f is a function of r, and r is a function of x and y. use r_x and r_y to denote the (partial) differentials of r wrt x, and wrt y, etc. use f' and f'' to deno
Read More: ...

how to prove sum of complex numbers z is zero when z^3=1

QUESTION: how to prove sum of complex numbers z is zero when z^3=1. I think that what you want is to show that the sum of the roots is zero. The cubic equation f(z) = z^3 - 1 = 0 has three roots, z1, z2, and z3 s.t. z1^3 =1, z2^3 = 1 and z3^3 = 1. We wish to show that z1 + z2 + z3 = 0. W
Read More: ...

Use principle of mathematical induction to 3 prove that n3 —n is divisible by 3

Let p(n) = n3 - n i)If n=1 , p(1 )  = 1^3 - 1                  [ 1^3 means 1 cube ]                        = 1 - 1                  
Read More: ...

Prove that if matrix A has an eigenvalue. ‘^ then matrix A^K (The k^th power of A)

prove that if a no. is a triplet than its 7 times. the cube root of the given no.
Read More: ...

What is the most accurate value of pie ?

Unfortunately, your answer isn't correct because pi starts 3.14159... You can find pi to a large number of decimal places by Googling it on the Internet. It has a decimal which goes on forever never repeating and is classed as a transcendental number and it's irrational.
Read More: ...

in triangle ABC PROVE THAT 1/r1+1/r2+1/r3=1/r

To Prove : 1/r1+1/r2+1/r3=1/r  LHS =>  1/(Δ/s-a) + 1/(Δ/s-b) + 1/(Δ/s-c)     = s-a/Δ + s-b/Δ + s-c/Δ  = (s-a+s-b+s-c)/Δ = {3s+ - (a+b+c)}/Δ = [3s - 2s]/Δ = s/Δ    { r = Δ/s } So s/Δ = 1/(Δ/s) = 1/r LHS = RHS
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0337 seconds